Congenital Ewing's Sarcoma/Peripheral Primitive Neuroectodermal Tumor: A Case Report and Review of the Literature - Shu-Guang Jin; Xiao-Ping Jiang; Lin Zhong (Elsevier, 2016)
Ewing's sarcoma (EWS) and peripheral primitive neuroectodermal tumor (pPNET) are small round cell malignancies that develop in soft tissue and bone. They very rarely affect newborns. A diagnosis of EWS/pPNET depends mainly on immunohistochemistry and molecular/genetic assays. Since these tumors are highly aggressive, patient prognosis is typically very poor, and treatment remains a challenge. Here, we report a 13-day-old newborn diagnosed with congenital EWS/pPNET and describe its treatment.